Skenario Penentuan Subsidi Silang Pada Perencanaan Anggaran Universitas PGRI Adi Buana Surabaya - Hayuningtyas, Rizcha Rahmawati; Widodo, Arifin Puji; Arifin, Mochammad (Jurnal JSIKA, 2013)
Abstract: PGRI Adi Buana University (UNIPA) Surabaya has ± 6000 amount of students who these is in six faculties. On the faculties there are some majors. Not all majors in demand by student candidates, so there are majors which has a little students and there are majors which has a many students. At this time the Faculty of Civil Engineering and Planning has decreased amount of students for the last 5-year period. Because the majority of the operating expenses from revenue students, so if amount of students was decrease that have an impact on the amount of income. On the faculty there is also an increase in expenses for the organization of the education plan for each period that led to reports of activity in the faculty experience minus. Based on the above issues, created a scenario determination of cross subsidy in the budget planning based on academic activities used in the analysis of the costs incurred by using Stand-Alone Cost (SAC) and Average Incremental Cost (AIC) approaches. With these models can be seen class variable costs, semivariabel costs, and fixed costs as well as the allocation process. The resulting output is a the model determination of cross subsidy in the budget planning of the Faculty of Civil Engineering and Planning. With this the determination of cross subsidy scenario, so can help the management to determine the sequence of processes that are arranged in generating the value of cross-subsidies necessary to balance the activity faculty report experiencing minus. Keyword: cross-subsidies, budget planning, the value of cross-subsidy